Avian mycobacteriosis in domestic chickens from selected agro-climatic regions in Ethiopia - Tadesse, S.; Woldemeskel, M.; Molla, B.; Tibbo, Markos; Kidane, D.; Medhin, G.; Britton, S. (2003)
Domestic poultry are important natural hosts of Mycobacterium avium (MAC), especially in the traditional poultry management system in the tropics. Qualitative and quantitative studies on a total of 95 chickens from three agro-climatic areas in Ethiopia were examined for avian mycobacteriosis through postmortem examinations and tissue staining (haematoxylin & eosin and acid-fast staining). The mycobacteria species were isolated and identified by using mycobacteriologic culture and experimental infection for virulence assessment. Five of the 95 examined chickens (5.3%) had gross tuberculous lesions in different visceral organs. On histopathologic examination, the lesions showed granuloma with typical Langhan’s giant cells in which acid-fast bacilli were shown by acid-fast stain. The culture on pyruvate-enriched Lowenstein-Jensen slants revealed growth of colonies on samples from 6 (6.3%) of the 95 chickens. Experimental infection with the strains from culture resulted in death of 10 (83.3%) of 12 inoculated chickens 56 to 110 days after inoculation, indicating that the isolates may be virulent strains of MAC. On postmortem examination, the experimentally infected chickens showed similar tuberculous lesions to natural infection that was confined at the site of injection, on the liver, spleen and (in two subjects) small intestine. The inoculated organisms were recovered from the respective organs. Therefore, this study showed that a virulent strain of MAC infects domestic chicken in Ethiopia.